Acute Response to Unilateral Unipolar Electrical Carotid Sinus Stimulation in Patients With Resistant Arterial Hypertension. Issue 3 (March 2016) - Heusser, Karsten; Tank, Jens; Brinkmann, Julia; Menne, Jan; Kaufeld, Jessica; Linnenweber-Held, Silvia; Beige, Joachim; Wilhelmi, Mathias; Diedrich, André; Haller, Hermann; Jordan, Jens
Abstract : Bilateral bipolar electric carotid sinus stimulation acutely reduced muscle sympathetic nerve activity (MSNA) and blood pressure (BP) in patients with resistant arterial hypertension but is no longer available. The second-generation device uses a smaller unilateral unipolar disk electrode to reduce invasiveness while saving battery life. We hypothesized that the second-generation device acutely lowers BP and MSNA in treatment-resistant hypertensive patients. Eighteen treatment-resistant hypertensive patients (9 women/9 men; 53±11 years; 33±5 kg/m 2 ) on stable medications have been included in the study. We monitored finger and brachial BP, heart rate, and MSNA. Without stimulation, BP was 165±31/91±18 mm Hg, heart rate was 75±17 bpm, and MSNA was 48±14 bursts per minute. Acute stimulation with intensities producing side effects that were tolerable in the short term elicited interindividually variable changes in systolic BP (–16.9±15.0 mm Hg; range, 0.0 to −40.8 mm Hg; P =0.002), heart rate (−3.6±3.6 bpm; P =0.004), and MSNA (−2.0±5.8 bursts per minute; P =0.375). Stimulation intensities had to be lowered in 12 patients to avoid side effects at the expense of efficacy (systolic BP, −6.3±7.0 mm Hg; range, 2.8 to −14.5 mm Hg; P =0.028 and heart rate, −1.5±2.3 bpm; P =0.078; comparison against responses with side effects). Reductions in diastolic BP and MSNA (total activity) were correlated ( r 2 =0.329; P =0.025). In our patient cohort, unilateral unipolar electric baroreflex stimulation acutely lowered BP. However, side effects may limit efficacy. The approach should be tested in a controlled comparative study. Abstract : Supplemental Digital Content is available in the text.